Kajian Pembuatan Cokelat Batang dengan Metode Tempering dan Tanpa Tempering - Eti Indarti; Normalina Arpi; Slamet Budijanto (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
This research is aimed to improve stability of milk chocolate bars by tempering process. The making of chocolate bars consisted of two formulations, namely a higher fat bar (40%) and low fat bar (21.5%).The study includes the chocolate bar preparation with and without tempering results. The melting point of milk chocolate bars that use cocoa butter tempering (L1) is higher than the milk chocolate bars that use fat without tempering (L2) for all treatments. Solid fat content (SFC) of F1 has higher solid phase at room temperature (55-60%) in all treatments compared with milk chocolate bar F2 (40-43%) and chocolate produced by UKM (Malaysia) 40-48 % and soccolatte 35-38% at the same temperature (350C). Blooming was not formed on the milk chocolate bars containing cocoa butter L1, while the milk chocolate bars showed blooming with L2 treatment.Keywords: chocolate bar, tempering, moulding, melting point, solid fat content, blooming